BLIMP1 transcriptionally induced by EGFR activation and post-translationally regulated by proteasome and lysosome is involved in keratinocyte differentiation, migration and inflammation. Issue 2 (November 2018) - Chang, Hua-Ching; Huang, Duen-Yi; Wu, Nan-Lin; Kannagi, Reiji; Wang, Li-Fang; Lin, Wan-Wan
Highlights: EGFR activation induces BLIMP1 mRNA and protein expression in keratinocytes via PKC, p38, and ERK signaling pathways. BLIMP1 protein can be downregulated by post-translational degradation through proteasome and lysosome in keratinocytes. BLIMP1 negatively regulates EGFR-mediated migration, IL8, CXCL5 and IL6 up-regulation, and K10 suppression in keratinocytes. Abstract: Background: B lymphocyte-induced maturation protein-1 (BLIMP1) is a transcriptional repressor, and plays a crucial role in the regulation of development and functions of various immune cells. Currently, there is limited understanding about the regulation of BLIMP1 expression in keratinocytes and crosstalk between EGFR and BLIMP1 in skin homeostasis. Objective: The aim of the study was to investigate the regulation and functional link between EGFR and BLIMP1 in human epidermal keratinocytes. Methods: Immunoblotting and Q-PCR were used to determine the molecular mechanism of BLIMP1 expression induced by EGFR in primary human epidermal keratinocytes (NHEK) and HaCaT cells. In functional assay, effects of BLIMP1 knockdown on EGFR-mediated cytokine production, differentiation, and migration in NHEK were evaluated by Q-PCR, ELISA, immunoblotting, and/or wound-healing assay. Results: EGFR activation by EGFR ligands could upregulate the protein and mRNA levels of BLIMP1 in NHEK and HaCaT cells. This effect was dependent on PKC, p38, and ERK activation. Additionally, the stability of BLIMP1 protein was under the control of the proteasome and lysosome degradation systems. EGF could also upregulate BLIMP1 expression in skin squamous cell carcinomas. In addition, BLIMP1 knockdown enhanced the EGFR-mediated IL8, CXCL5 and IL6 gene expression and keratinocyte migration, but reduced the EGFR-mediated suppression of differentiation marker K10. Conclusions: Our findings shed new insights into the regulation of BLIMP1 expression by EGFR-mediated gene transcription and proteasome/lysosome-mediated degradation in keratinocytes. Functionally, BLIMP1 is a negative regulator of EGF-induced inflammation and migration in keratinocytes, and exerts a gene-specific regulation on keratinocyte differentiation.